Pengembangan kompetensi profesional Guru Pendidikan Jasmani Olahraga dan Kesehatan melalui Aktivitas Musyawarah Guru Mata Pelajaran (MGMP) - Muliadi Muliadi (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The quality of education in Indonesia is determined by several factors, one of them is professional teacher. Professional teachers are those who have the ability to deliver subject matter in depth and comprehensive. The teacher proffesionalism can be developed through a professional organization. In relation to this matter, the Subject Teacher Working Group (MGMP) is a professional organization with a legal body that aims to develop teacher professionalism. The activities carried out by Physical Education Teacher Working Group as an effort to improve the quality of education and develop teacher competencies are: a) conducting curriculum deepening, b) developing syllabus, c) developing lesson plan, d) developing teaching materials, e) creating and implement- ing analysis instructional materials, f) developing assessment systems, g) compiling exam content outlines and questions, h) developing learning models, i) informing and implementing learning. The Physical Education Teacher Working Group in schools has an important role in the development of professional competencies, providing solutions to overcome the problems experienced during the Physical Education learning process, both at the primary, junior high and high school level. Some of these problems include limited infrastructure and facilities, low quality of teaching orirrelevant learning models to the physical and mental development of students.